Metabolic reprogramming of cancer-associated fibroblasts by TGF-β drives tumor growth: Connecting TGF-β signaling with "Warburg-like" cancer metabolism and L-lactate production - Guido, Carmela; Whitaker-Menezes, Diana; Capparelli, Claudia; Balliet, Renee; Lin, Zhao; Pestell, Richard G.; Howell, Anthony; Aquila, Saveria; Andò, Sebastiano; Martinez-Outschoorn, Ubaldo; Sotgia, Federica; Lisanti, Michael P. (Cell cycle (Georgetown, Tex.), 2012)
We have previously shown that a loss of stromal Cav-1 is a biomarker of poor prognosis in breast cancers. Mechanistically, a loss of Cav-1 induces the metabolic reprogramming of stromal cells, with increased autophagy/mitophagy, mitochondrial dysfunction and aerobic glycolysis. As a consequence, Cav-1-low CAFs generate nutrients (such as L-lactate) and chemical building blocks that fuel mitochondrial metabolism and the anabolic growth of adjacent breast cancer cells. It is also known that a loss of Cav-1 is associated with hyperactive TGF-β signaling. However, it remains unknown whether hyperactivation of the TGF-β signaling pathway contributes to the metabolic reprogramming of Cav-1-low CAFs. To address these issues, we overexpressed TGF-β ligands and the TGF-β receptor I (TGFβ-RI) in stromal fibroblasts and breast cancer cells. Here, we show that the role of TGF-β in tumorigenesis is compartment-specific, and that TGF-β promotes tumorigenesis by shifting cancer-associated fibroblasts toward catabolic metabolism. Importantly, the tumor-promoting effects of TGF-β are independent of the cell type generating TGF-β. Thus, stromal-derived TGF-β activates signaling in stromal cells in an autocrine fashion, leading to fibroblast activation, as judged by increased expression of myofibroblast markers, and metabolic reprogramming, with a shift toward catabolic metabolism and oxidative stress. We also show that TGF-β-activated fibroblasts promote the mitochondrial activity of adjacent cancer cells, and in a xenograft model, enhancing the growth of breast cancer cells, independently of angiogenesis. Conversely, activation of the TGF-β pathway in cancer cells does not influence tumor growth, but cancer cell-derived-TGF-β ligands affect stromal cells in a paracrine fashion, leading to fibroblast activation and enhanced tumor growth. In conclusion, ligand-dependent or cell-autonomous activation of the TGF-β pathway in stromal cells induces their metabolic reprogramming, with increased oxidative stress, autophagy/mitophagy and glycolysis, and downregulation of Cav-1. These metabolic alterations can spread among neighboring fibroblasts and greatly sustain the growth of breast cancer cells. Our data provide novel insights into the role of the TGF-β pathway in breast tumorigenesis, and establish a clear causative link between the tumor-promoting effects of TGF-β signaling and the metabolic reprogramming of the tumor microenvironment.